The effect of inflation and the economy during the Pandemic years: A Methodological Proposal for Sentiment Analysis in Python - Bernábe Loranca , Maria Beatriz; Mendoza Bernabe , Melissa; Carrillo Canán , Alberto (International Journal of Combinatorial Optimization Problems and Informatics, 2026)
In this work, NLP Natural Language Processing has been used, specifically sentiment analysis for the problem "The effect of inflation and the economy during the pandemic years" using as a database a tweet written between the dates 01 - 01-2020 to 10-11-2022. The objective is to classify tweets as positive, negative and neutral and establish the impact of some factors related to the economy after the Covid-19 pandemic. A prediction was made based on historical data, on how inflation could be modified in the period 2025-2028. This analysis provides a method to track public inflation expectations by tracking opinions from rich network data. Smart citations: https://scite.ai/reports/10.61467/2007.1558.2026.v17i2.1257 Dimensions. Open Alex.